POSSIBILITIES OF AUTOMATIC RECOVERY OF POWER SUPPLY IN DISTRIBUTION NETWORK IN CASE OF MULTIPLE SIMULTANEOUS FAULTS - I. Golovinskii (Вестник Северо-Кавказского федерального университета, 2022)
We study the possibilities of automatic restoration of power supply after a set of simultaneous sustained faults on power lines in the distribution network. For circuits of the double line type with double-sided power supply, a necessary and sufficient condition is given for prompt (through switching) recoverability of the power supply to all consumers in case of multiple faults before the damaged equipment is repaired. When planning repairs, we suggest using a graph of islands of the fault-free equipment.